Performance and Sharia Assessment of Islamic Coin (ISLM): Evidence from Forecasting, Risk-Adjusted Returns and Regulatory Analysis - Anita, Anita; Suganda, Asep Dadan; Fhathunnida, Ratu; Hafeez, Humaira (IAIN Manado, 2026)
The growth of Sharia-compliant crypto assets has prompted the need for an empirical study on the feasibility of Islamic Coin (ISLM) as a Sharia-compliant investment instrument. This study aims to analyze the performance of Islamic Coin (ISLM) as a Sharia-compliant investment asset through risk-adjusted return measurements, volatility forecasting, and a normative review of Sharia compliance and regulations. The study employed a mixed methods approach with a sequential explanatory design. The quantitative analysis utilized daily time series data for the period December 2023–October 2025 using the Sharpe index, independent t-test, and the Autoregressive Integrated Moving Average (ARIMA) model. The qualitative analysis employed a normative-juridical approach based on fatwas, maqasid al-shariah, and the Sharia governance framework. The results show that Islamic Coin (ISLM) has the highest Sharpe value compared to Sharia-compliant stocks and gold, indicating a potentially better return relative to risk. However, statistical difference tests showed no significant difference between the three instruments, so ISLM's superiority is relative and not supported inferentially. The ARIMA (7,1,0) model produced a good level of forecasting accuracy with a MAPE value of 3.06%, although high volatility indicates persistent speculative risk. From a normative perspective, Islamic Coin (ISLM) has the potential to conditionally comply with Sharia principles as long as it meets the transparency, underlying asset, and adequate Sharia governance aspects. This study concludes that Islamic Coin (ISLM) is more appropriately positioned as a complementary instrument (satellite asset) in a Sharia portfolio rather than as a superior investment asset, with its suitability determined by risk management and the integrity of Sharia governance.